'A platform for goodness, not for badness': The heuristics of hope in patients' evaluations of online health information. (August 2022) - Petersen, Alan; Schermuly, Allegra; Anderson, Alison
Abstract: Patient advocates and activists are increasingly relying on online health information that can assist them to manage their health condition. Yet once online, they will confront diverse information whose veracity and utility are difficult to determine. This article offers a sociological analysis of the practical methods, or heuristics, that patient advocates and activists use when making judgements about the credibility and utility of online information. Drawing on the findings from interviews with fifty Australian patient advocates and activists, it is argued that these individuals' use of these heuristics reflects their hopes that information can help them manage their condition which may, in some cases, override fears and uncertainties that arise during searches. The article identifies the common 'rules-of-thumb'—or what we call the 'heuristics of hope'—that patient advocates/activists may use to make judgements and highlights the dangers of over-reliance on them, especially regarding clinically unproven, potentially unsafe treatments. Analyses of the heuristics of hope, we conclude, can assist in understanding the dynamics of decision-making and the role that affect plays in online patient communities which is crucial in an age characterised by the rapid circulation of emotionally charged messages, often based on hope. Highlights: Heuristic analysis can help explain patients' evaluations of online information. Patients' online searches and evaluations are guided by the heuristics of hope. Reliance on the heuristics of hope may mislead patients, predisposing them to harms.